2015
DOI: 10.3892/etm.2015.2495
|View full text |Cite
|
Sign up to set email alerts
|

Safety of tirofiban for patients with acute ischemic stroke in routine clinical practice

Abstract: Abstract. The aim of the present study was to investigate the safety of tirofiban alone and in combination with various treatments in acute ischemic stroke (AIS). A total of 120 patients with AIS were included in the study, and these patients were divided into three treatment groups: Group A (tirofiban alone, n=68), group B (tirofiban plus thrombolytic therapy, n=26), and group C (tirofiban as a 'bridging therapy', n=26). Risk factors, stroke severity, initial imaging, treatment regimens, complications and lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The progression occured on average 27.85 hours (6-72 hours) after the onset of stroke symptoms. The average NIHSS score at hour 1 of admission was 7.14 (2-6); the score at the time of progression occurence was 10.21 (5-21) with an average NIHSS increase of 3.07 (2-11); at 24 hours after administration of tirofiban, the score was 9.79 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and on discharge the score was 9.46 (1-18) (Figure 1). In the evaluation of the patient groups in terms of stroke subtypes, the NIHSS score was found to be highest in the cardioembolic stroke group and lowest in the small vessel disease group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The progression occured on average 27.85 hours (6-72 hours) after the onset of stroke symptoms. The average NIHSS score at hour 1 of admission was 7.14 (2-6); the score at the time of progression occurence was 10.21 (5-21) with an average NIHSS increase of 3.07 (2-11); at 24 hours after administration of tirofiban, the score was 9.79 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and on discharge the score was 9.46 (1-18) (Figure 1). In the evaluation of the patient groups in terms of stroke subtypes, the NIHSS score was found to be highest in the cardioembolic stroke group and lowest in the small vessel disease group.…”
Section: Resultsmentioning
confidence: 99%
“…In an another study which compared Tirofiban monotherapy, trombolytic treatment and interventional treatment, bleeding complication was not observed in tirofiban group but recanalization rate was found lowly (25%) compared to other groups (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet function returned in 2 hours when stopped, 46 which might make tirofiban a more desirable glycoprotein IIb/IIIa receptor inhibitors in AIS. Acceptable safety outcomes and more favourable function outcomes have been reported in small case series of AIS treated with tirofiban alone, 47 tirofiban in combination with intravenous or IA thrombolysis 47–49 and tirofiban in combination with bridging therapy, 50 51 respectively. In a prospective, randomised, placebo-controlled, open-label treatment phase II trial, tirofiban did not increase the risk of cerebral haemorrhagic transformation (HT) and parenchymal haemorrhage but may decrease the mortality rate at 5 months.…”
Section: Impact Of Aetiological Mechanisms Underlying Lao On Choice Omentioning
confidence: 94%
“…53 Nonetheless, especially tirofiban is discussed controversially regarding its use in AIS patients, since some studies showed the safety and efficacy of this drug in patients with rescue stenting, using tirofiban alone or together with standard thrombolytic therapy. 54,55 In conclusion, despite the high potency of anti-GPIIb/IIIa treatment in patients with AMI and some promising clinical studies using tirofiban in a certain subgroup of ischemic stroke patients, this receptor has to be considered as unreliable, yet druggable target in the therapy of ischemic stroke (►Table 1). Very importantly, these data provide strong evidence that platelet aggregation may not be of major significance for thrombo-inflammation and immune cell recruitment in the infarcted brain, implicating that other platelet-dependent mechanisms are responsible for the pathological progress of I/RI in AIS.…”
Section: Targeting Gpiib/iiia In Ischemic Strokementioning
confidence: 99%